Penyimpangan Digital: Penggunaan Instagram sebagai Media Pemasaran Narkoba di Indonesia - Riky Novarizal; Dean Rizki Saputra; Rahmat Amin Siregar (Deviance Jurnal Kriminologi, 2025)
This study examines how Instagram serves as a digital marketplace for narcotics in Indonesia, highlighting how online anonymity and networked promotion facilitate illicit transactions. The research aims to describe the mechanisms by which narcotics are marketed through Instagram, the characteristics of dealer accounts, and the driving factors behind this phenomenon. Using a digital ethnography approach, the study analyzed over 1,500 Instagram posts under hashtags such as #duniakiri and #infoduniapersilatan, complemented by a review of relevant scholarly literature. The findings indicate that drug dealers employ coded language, region-based hashtags, and anonymous accounts to conceal their activities, primarily promoting their products through Instagram Stories rather than public feeds. The study identifies four major drivers: online anonymity, partnership models between accounts, wide promotional reach, and efforts to build buyer trust. These patterns demonstrate how digital platforms enable traditional criminal practices to adapt to the online environment, reducing risk and increasing reach. The results affirm the relevance of Jaishankar’s Space Transition Theory, emphasizing that digital crime represents an extension of conventional deviance shaped by technology. This research recommends stronger digital surveillance and increased awareness of cybercrime as key measures to address the evolving landscape of the online drug trade.